Identification of a novel compound that inhibits osteoclastogenesis by suppressing nucleoside transporters. Issue 8 (3rd April 2016) - Katsuyama, Shun; Sugino, Kumi; Sasazawa, Yukiko; Nakano, Yoshihiko; Aono, Harumi; Morishita, Keisuke; Kawatani, Makoto; Umezawa, Kazuo; Osada, Hiroyuki; Simizu, Siro
Abstract : We screened small‐molecule compounds that inhibit osteoclast differentiation to find new anti‐osteoporosis agents and found that a novel compound, SUKU‐1, suppressed osteoclastogenesis. We also synthesized 38 derivatives of SUKU‐1 and discovered that nine of them had inhibitory effects on osteoclastogenesis and that SUKU‐33 was the most potent inhibitor. Next, we investigated the mechanisms by which SUKU‐33 suppressed osteoclast differentiation. By measuring the uptake of [ 3 H]‐uridine in cells, we found that SUKU‐33 suppressed both equilibrative nucleoside transporters and concentrative nucleoside transporters. These results suggest that SUKU‐33 inhibits osteoclast differentiation by suppressing nucleoside transporters. Abstract : We screened small‐molecule compounds that inhibit osteoclastogenesis using a chemical library. SUKU‐33 is a potent inhibitor targeting osteoclasts by the derivatization of an osteoclastogenesis inhibitor we found. SUKU‐33 inhibits both equilibrative nucleoside transporters and concentrative nucleoside transporters to suppress osteoclast differentiation.